Evaluation of the therapeutic efficacy of clindamycin in patients hospitalised with erysipelas - de Godoy, José Maria Pereira; Oliveira, André Luís Cozetto de; Godoy, Maria de Fátima Guerreiro (Medical Studies/Studia Medyczne, 2017)
Introduction : Erysipelas is an acute skin infection of a streptococcal-related aetiology. Penicillin is the first-line antibiotic in the treatment of erysipelas; however, a number of other antibiotics are used. Aim of the research : To evaluate the clinical response of erysipelas to clindamycin in hospitalised patients. Material and methods : A retrospective cohort study was performed of all patients hospitalised with erysipelas and treated with the antibiotic clindamycin in Hospital de Base, São José do Rio Preto between 2000 and 2008. Results : The efficacy of this medication was evaluated. Failure of clinical treatment was detected in 4% of the 50 patients treated with clindamycin, but no failure was seen in 51 patients who were treated with clindamycin combined with other antibiotics. Conclusions : Clindamycin is clinically efficacious (96%) to treat patients hospitalised for erysipelas. Clindamycin is a good therapeutic option.